Structural and Photoelectrochemical Characterization of Heterostructured Ag2MoO4-SnS2 coated Carbon Sheet Photocapacitor - Thirunavukarasu, K.; Yuvapragasam, A.; Rasalingam, S.; Velauthapilla, Dhayalan; Ravirajan, P.; Senthilnanthanan, M. (University of Jaffna, 2019)
Photocapacitors that can harvest solar energy and store it in the form of electrical energy, are expected to solve the problem of unstable power output of solar cells under fluctuating sunlight. In the present study, a novel heterostructured Ag2MoO4-SnS2 photocapacitive device was developed. In this device, SnS2 nanoparticles act as capacitive platform via redox pseudocapacitance, whereas Ag2MoO4 molecules act as the active core of the device. The crystalline structure and the surface morphology of Ag2MoO4-SnS2 coated carbon sheet was examined by powder X-ray Diffraction method (XRD) and Scanning Electron Microscopy (SEM) respectively. The XRD pattern indicates that Ag2MoO4 coated on carbon sheet is in β phase with respect to Ag2MoO4. The SEM analysis reveals Ag2MoO4 coated carbon sheet as hexagonal nanorods, and Ag2MoO4- SnS2 coated carbon sheet as spherical nanoparticles. The device, when subjected to visible light illumination, showed a specific capacitance of 780 mF/cm2 with an open circuit potential of 0.8 V vs Ag/AgCl electrode. The high capacitance obtained with this novel device may be attributed to the large specific area and high conductivity of the Ag2MoO4- SnS2 coated carbon sheet. This research study has open up a new avenue for an effective heterostructured photocapacitor.
Keywords: Photocapacitor; photoelectrochemical characterization; specific capacitance; silver molybdate; carbon sheet